Limited temporal response of Cerrado mammals to anthropogenic pressure in areas under distinct levels of protection. (20th February 2022) - Ferreira, G. B.; Newbold, T.; Oliveira, M. J. R.; Pringle, H.; Pinheiro, M. S.; de Pinho, F. F.; Carbone, C.; Rowcliffe, M.
Abstract: Anthropogenic pressure has well‐documented effects on the spatial distribution of biodiversity but it can also have more subtle effects on wildlife, influencing the time of the day and for how long animals are active. These temporal effects have not received much attention from the scientific and conservation community, despite activity being intrinsically related to crucial aspects in an animal's life. Here we use data from a large‐scale camera trap survey (517 survey sites covering more than 1000 km 2 ) conducted in areas under distinct levels of protection in the Brazilian Cerrado to investigate the effect of anthropogenic pressure on the activity of mammal species >1 kg. We used both circular statistics and GLMMs to investigate whether species would shift activity towards the night in response to disturbance, resulting in a decrease of diurnal activity in areas under lower protection levels and closer to households. Our results revealed that most species investigated did not show a temporal response to anthropogenic pressure, with only two species responding in the way we expected: tamanduas reduced the probability of daytime activity closer to households and collared peccaries reduced diurnal activity slightly in areas under lower protection levels. Our findings also suggest that environmental factors have a greater influence on species' activity than indicators of pressure in the mosaic of protected areas studied. Although stricter levels of habitat protection are known to have a positive and strong influence on the spatial distribution of many mammal species in the study region, we showed here that human pressure has only a modest effect on the period these species were active. This limited temporal response highlights the need for large natural areas under low disturbance that allow mammal species to respond spatially to threats. Abstract : We used camera trap data to investigate whether Cerrado mammals would shift part of their activity towards the night in response to anthropogenic pressure. Our results revealed that 12 out of 14 species investigated did not show a temporal response to pressure. Only two species responded in the way we expected: tamanduas reduced the probability of daytime activity closer to households and collared peccaries reduced diurnal activity slightly in areas under lower protection levels.